Characterization and early detection of tan spot disease in wheat in vivo with chlorophyll fluorescence imaging - Kenny, Paul (Acta Biologica Szegediensis, 2011)
Plant growth is affected by various factors. The resistance of the plant to withstand various biotic and abiotic stress factors plays a vital role for its growth and development. In this study, we have characterized the resistance of various wheat cultivars to tan spot disease by the application of imaging techniques (such as: digital photography, chlorophyll fluorescence) under controlled conditions. The increase of the F0 chlorophyll fluorescence indicates the production of free chlorophylls, which may be involved in the defense reaction against the pathogen. The fluorescence data revealed changes of the photosynthetic apparatus at an early stage before the appearance of visual symptoms appeared, which could be used as an easily measurable markers of the infection.